1978
DOI: 10.1017/s132335800001540x
|View full text |Cite
|
Sign up to set email alerts
|

Radio Evidence on the Particle Distribution Functions in the Corona following Flares

Abstract: In this paper we summarize the results of radio studies of the distribution functions (number, energy distribution and pitch angle distribution) of the energetic particles that are produced at the time of solar flares. We consider the clues and constraints they impose on the mechanisms of acceleration, bearing in mind that radio evidence implies that there are at least two stages of acceleration in many flares.In the following sections we discuss the distribution functions of the particles resulting from (a) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Dulk et al, 1978). Yet Langmuir-wave conversion, although its exact mechanism is controversial, could resolve the difficulties discussed in the previous section.…”
Section: A Langmuir-wave Theory Of Moving Type IV Emissionmentioning
confidence: 99%
“…Dulk et al, 1978). Yet Langmuir-wave conversion, although its exact mechanism is controversial, could resolve the difficulties discussed in the previous section.…”
Section: A Langmuir-wave Theory Of Moving Type IV Emissionmentioning
confidence: 99%
“…The accepted interpretation for type IV M bursts is the one based on gyrosynchroton emission from mildly relativistic electrons trapped in a discrete plasmoid ejected from the Sun (Wild et al, 1963, Riddle, 1970Dulk, 1973 ;Dulk et al, 1978;Kai, 1978). However, the observations of very bright type IV M sources reported (Stewart et al, 1978;Duncan et al, 1980) render the interpretation based on gyrosynchroton mechanism doubtful (McLean, 1974;Duncan et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Most non-moving solar metre-wave bursts have long been attributed to the excitation of Langmuir waves by energetic electrons and the conversion of a portion of these Langmuir waves to electromagnetic waves (Wild 1950;Ginzburg and Zheleznyakov 1958). However, this process has been almost universally rejected as an explanation of moving Type IV emission (Dulk et al 1978). There have been two main arguments for this rejection:…”
Section: Introductionmentioning
confidence: 99%
“…However, from measurements made with one-dimensional interferometers it has been concluded that moving Type IV sources show no dispersion of source position with observing frequency (Wild et al 1959;Boischot and Clavelier 1968;Dulk 1973). Moving Type IV solar radio sources have therefore been attributed instead to gyrosynchrotron emission from mildly relativistic electrons trapped on a plasmoid -a 'magnetic smoke ring' in Riddle's (1970) words -ejected from the Sun (Boischot 1957;Wild et al 1963;Dulk et al 1978;Kai 1978).…”
Section: Introductionmentioning
confidence: 99%